Development of Individual Learners: Perspective on the Uncertain Future Contribution of E-Learning - Ahmad Dahlan, Zaki; Othman, Nor Arzami; Mohd Idris, Mohd Fazril Izhar; Jusoff, Kamaruzaman (2009)
E-learning in the educational world has grown and changed rapidly in recent years. Both private and public sector organizations have embraced the practice of reaching their students at a distance via new technologies afforded them by Information Communication Technology (ICT) infrastructure. E-learning is grounded on technology, and without it, its practice would be difficult, if not impossible. We can see that the use of the internet and ICT are becoming an important part of learning and teaching strategies in many educational institutions. Knowing that education has always been an important engine for economic development, the Malaysian government has taken initiative steps to implement public awareness on the ICT issues. An important part of e-learning has been to contribute to the development of individual learners whatever their life circumstances. E-learning as a field of educational endeavor is at a crucial juncture in its historical development. The notion of learning at a distance has gained wide acceptance across the developed world. Instructors, physically and temporally separated from learners using newly emerging information and communication technologies, are widespread. The potential of latest technology has adopted in creating new learning environments. The rational behind this endeavor is the expectation that unique features of the Information Communication technology. It also can include a range of powerful media forms and its interactive capability that support sophisticated range and interaction in teaching. As a result, these approaches will provide a rich environment for teaching.